'Treatment - a handbook of drug therapy'. Issue 19 (11th September 1981) - Unknown
Abstract : 'Treatment' is a two-volume loose-leaf updatable book 1 designed for general practitioners. With our copy came over 60 updating pages for each volume. Replacing out-of-date pages is necessary though tedious. Each volume has its own index.